EVALUATION OF THE QUALITY OF TOMATO SEED POPULATIONS FROM THE ORGANIC PRODUCTION SYSTEM DURING AGING - Poštić, Dobrivoj (Journal on Processing and Energy in Agriculture, 2020)
A total of six tomato seed populations, collected in the autumn of 2016 at different locations in Serbia (West (3), South (1), North (1) and East (1)), were enrolled in this study. Seeds of the tomato populations considered were produced in the organic growing system in the area of Zaovice (76 m a.s.l., chernozem), Stara Pazova, Northern Serbia (44˚ 47 '19.6" N, 20˚ 27' 56.2" E) in 2017. Analyses of the germination parameters of the tomato seed populations examined (namely the germination energy, total germination, abnormal seedlings and dead seeds of the tomato seeds considered) indicated significant (р < 0.01) differences according to the production year (A) and the tomato seed population (B). The impact interactions (р < 0.01) of these factors (A × B) proved significant only relative to dead seeds. A highly significant positive correlation was found between the germination energy and the total germination of the seeds considered (r = 0.8711, p < 0.001), as well as between the amounts of their abnormal seedlings and dead seeds (r = 0.92297, p < 0.001). The germination energy and the total germination of the tomato seeds considered were found to decrease with the increasing seed age, in contrast to the numbers of their abnormal seedlings and dead seeds which continued to increase with seed aging.
Keywords: tomato, germination seeds, population/variety